Ban or no, let's keep a lid on the other 'silent killer' - Abd Razak, Dzulkifli (2007)
The ban, albeit a limited one, seems to be on after all. This followed the Health Ministry's change of heart on an earlier proposal to ban advertising related to fast food in general. In the words of the Health Minister: "The time has come." Of concern is the increasing number of Malaysians with chronic lifestylerelated diseases. Among the 26 million citizens, one in three aged 30 and above is said to suffer from highblood pressure. One in four is over weight or obese. One in 10 has diabetes, while about one in 15 has high cholesterol. Significantly, the percentage of obese Malaysians doubled what it was a decade ago. Aptly, Malaysia has earned the dubious honour of being the "fattest" Asian nation.